1776 - Warner, Jack L., 1892-1978.; Stone, Peter, 1930-; Hunt, Peter H.; Daniels, William, 1927-; Da Silva, Howard, 1909-1986; Howard, Ken, 1944-; Danner, Blythe; Vestoff, Virginia; Madden, Donald, 1933-1983.; Stradling, Harry, 1925-; Edwards, Sherman; Ostrow, Stuart, 1932-; et al. (Culver City, CA : Columbia TriStar Home Entertainment, 2002)
1776 is a delightful musical celebration of the founding of The United States of America. The story centers around the familiar historical characters as they organize a movement for independence from Mother England. All events lead up to that most significant date, July 4, 1776, when the Declaration of Independence was signed. This is the DVD "restored" version which runs ca. 166 minutes -- longer than the theatrical release cut, yet shorter than the laserdisc "restored" version.
Book by Peter Stone. Based on the musical play "1776" produced on the New York stage by Stuart Ostrow.
Special features: director and screenwriter commentary, screen tests, bonus trailers, production notes.
Director of photography, Harry Stradling, Jr. ; music and lyrics, Sherman Edwards ; based on a conception by Sherman Edwards ; choreography, Onna White.
William Daniels, Howard Da Silva, Ken Howard, Donald Madden, Blythe Danner, John Cullum, Roy Poole, David Ford, Virginia Vestoff, Ron Holgate, Ray Middleton, John Myhers, Rex Robbins, William Duell.
Rated PG.
DVD, Region 1 encoding.
Keywords: Stone, Peter, -- 1930- -- Film and video adaptations; Adams, John, -- 1735-1826 -- Drama; Franklin, Benjamin, -- 1706-1790 -- Drama; Jefferson, Thomas, -- 1743-1826 -- Drama; United States. -- Drama; Feature films; Feature films -- United States; Historical films; Musical films; Video recordings for the hearing impaired